Proposed Implementation of an Integration Inventory Model to Supply Chain System involving Supplier, Manufacture and Buyer. (Study Case: PT. X) - Ulum, Rikzan Bachrul (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2018)
PT. X has the problem of how to maintain the stability of the costs charged to each party involved in the supply chain system. In order not to happen one party burden excess costs compared to the other party. The purpose of this research is to determine the optimal number of delivery frequency for customer; determine the optimal delivery quantity of the manufacturing for the customer; determining optimal quantity order from customer, optimal production quantity from manufacturing and optimal material order quantity for supplier; determining total cost of inventory on costumer, total inventory cost at manufacture and total total cost of optimal inventory. With the method used is the application of inventory model integrated in supply chain system involving suppliers, manufacturers and costumer. The results of research can be, the number of optimal delivery frequency is 52 times; The optimal manufacturing quantity delivery for costumer is 659 units; Order quantity of customer is 34,245 units, production quantity from manufacturing is 1,317 units and material order quantity for supplier is 1,317 units; and Total cost of inventory at costumer that is Rp. Rp 17,641,430, -, total inventory cost in manufacturing Rp 28.104.522, - and total cost Rp 45.536.792, -. Thus, if this inventory model can run successfully, will be able to reduce the total cost of inventory on the costumer of Rp. 338,142,997,50 can be saved by 95% to Rp 17,641,430, -, and for total inventory cost in manufacture from Rp 627,979,825.50 can be saved by 96% to Rp 28,104,522, - and the total total inventory cost from Rp 966.122.850, - can be saved by 95% to Rp 45,536,792.